Comparative Efficacy of Novel Biomimetic Remineralising Technologies - Peiyan Shen; James R. Fernando; Yi Yuan; Coralie Reynolds; Eric C. Reynolds (Biomimetics, 2023)
Biomimetic technologies for the remineralisation of enamel subsurface lesions (ESLs) have been developed and include: fluorocalcium phosphosilicate bioglass (BG/F); casein phosphopeptide-amorphous calcium phosphate (CPP–ACP) and with fluoride (CPP–ACFP); and self-assembling oligopeptide P11-4 (SAP). The aim of this study was to compare the remineralisation of ESLs in vitro using these technologies. Human enamel slabs with ESLs were cut into two half-slabs; one half-slab was untreated (control), and the other half was treated by exposure to one of the four technologies with artificial saliva (AS) or AS alone for 14 days at 37 °C. The technologies were applied to the ESL surface according to the manufacturer’s instructions. At the completion of each treatment, the treated half-slabs and their paired control half-slabs were embedded, sectioned and the mineral content was determined using transverse microradiography. The change in mineral content (remineralisation) between treatments was statistically analysed using one-way ANOVA. The order from highest to lowest remineralisation was CPP–ACFP (52.6 ± 2.6%) > CPP–ACP (43.0 ± 4.9%) > BG/F (13.2 ± 2.5%) > SAP (5.8 ± 1.6%) > AS (2.1 ± 0.5%). Only CPP–ACFP and CPP–ACP produced remineralisation throughout the body of the lesions. All four biomimetic technologies had some effect on the remineralisation of ESLs; however, CPP–ACFP with calcium, phosphate and fluoride ions stabilised by CPP was superior in the level and pattern of remineralisation obtained.